Action at a distance on object-related ventral temporal representations. (August 2019) - Lee, Dongha; Mahon, Bradford Z.; Almeida, Jorge
Abstract: The representation of objects in ventral temporal cortex is relatively resilient to transformations in the stimuli. There is emerging recognition that ventral temporal object representations are forged via interactions among a broader network of regions that receive independent inputs about a stimulus. Here we test whether ventral temporal representations are causally modulated by disrupting processing in distal associative areas. We used transcranial direct current stimulation (tDCS) to stimulate left parietal areas and functional Magnetic Resonance Imaging (fMRI) to measure object-related neural responses in the ventral stream. We find that representational geometries and category discriminability within ventral temporal cortex, as well as functional connectivity between ventral temporal and parietal areas, are enhanced by anodal compared to cathodal stimulation of left parietal associative cortex. These results demonstrate that ventral temporal representations can be causally modulated by processing distal to the ventral stream.